Einstein–Bohr recoiling double-slit gedanken experiment performed at the molecular level. (August 2015) - Liu, X-J; Miao, Q; Gel'mukhanov, F; Patanen, M; Travnikova, O; Nicolas, C; Ågren, H; Ueda, K; Miron, C
Synopsis: Double-slit experiments illustrate proof for wave–particle complementarity. The essence of Einstein–Bohr's debate about wave–particle duality was whether the momentum transfer between a particle and a recoiling slit could mark the path, thus destroying the interference. We realized this recoiling double-slit gedanken experiment by resonant X-ray photoemission from molecular oxygen for geometries near equilibrium (coupled slits) and in a dissociative state far away from equilibrium (decoupled slits). Interference is observed in the former case, while the electron momentum transfer quenches the interference in the latter case.